Por Llanos y Montañas: Creemos en la Historía: An Inquiry into the 1961 Cuban Literacy Campaign using Photographic Representation - Joanne C. Elvy (University of Windsor, 2011)
In 1961, the Revolutionary government in Cuba initiated a literacy campaign that became the vehicle for social change in the country, affirming the value of education, healthcare, citizenship, professional development and the concept of family and community. As an artful researcher revisiting the impact of this educational initiative, my intent was to incorporate photographs into my research as a kind of language, a felt knowledge. Photography thus became a vital part of my methodological process as an important research and presentation tool, in respect to my engagement as a researcher from outside the Cuban experience, together with the audience's interaction with the resulting images (Cixous, Barthes, Jongeward, Robins, et al). The photograph has also been a metaphor for the complexity of how Cuba is understood within an historical context; in how it deflects from linear readings of past events, into a space where stories can be revisited as part of a shared experience (Irwin-Zarecka, Steedman, Thelen, et al).